1971
DOI: 10.1159/000264575
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Temporal Summation of Central Retinal Areas in Normal People of All Ages

Abstract: Temporal summation as the relation of threshold intensity to presentation time of a stimulus has been tested in different retinal locations under photopic and mesopic conditions in 35 normal subjects of all ages. The characteristics of temporal summation is quite independent of age, retinal location and adaptation of the eye. The only variable is the time of transition from complete to absent temporal summation, ranging from 32 msec in photopic foveal vision to more than 320 msec in mesopic peripheral vision

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 4 publications
4
19
0
Order By: Relevance
“…The present finding is consistent with several one-pulse studies that showed longer critical durations or more integration in the periphery than in the fovea (Dannheim & Drance, 1971;Ronchi & Novakova, 1971;Sperling & Jolliffe, 1965). Moreover, our results are in line with numerous investigationsof retinal loci with respect to temporal resolution, which can be viewed as the upper limitmg case of temporal integration.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The present finding is consistent with several one-pulse studies that showed longer critical durations or more integration in the periphery than in the fovea (Dannheim & Drance, 1971;Ronchi & Novakova, 1971;Sperling & Jolliffe, 1965). Moreover, our results are in line with numerous investigationsof retinal loci with respect to temporal resolution, which can be viewed as the upper limitmg case of temporal integration.…”
Section: Resultssupporting
confidence: 93%
“…Although most of these investigations indicate longer critical durations or more integration for peripheral than for foveal stimulation (Sperling & Jolliffe, 1965;Dannheim & Drance, 1971;Ronchi & Novakova, 1971), one study (Van den Brink & Bouman, 1954) has shown that temporal integration is independent of retinal locus. The latter study differed from the former in two major respects.…”
mentioning
confidence: 99%
“…Across different spatial summation functions, the only two parameters that varied were the peak spatial frequency and the peak sensitivity of the filter. The suitability of the template was evaluated by fitting 59 data sets from six classic perimetric studies of spatial summation in normal eyes (Dannheim & Drance, 1971;Johnson, Keltner, & Balestrery, 1978;Kasai, Takahashi, Koyama, & Kitahara, 1993;Latham, Whitaker, Wild, & Elliott, 1993;Sloan, 1961;Wilson, 1970), as shown in Figure 4. We used decibel rather than log units in this figure to be consistent with the Figure 2.…”
Section: Empirical Templatementioning
confidence: 99%
“…Conversely, in reference to the kinetic method, the increase in speed of the test and in information content of the visual field charts is counteracted by lower precision due to response dependence on latency time (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%